Crop catalogue of farmers’ preferred crop cultivars and varieties in western Kenya - Niane, Abdoul Aziz; Otieno, Gloria; Nyambok, Anne; Aluso, Lillian; Kemal, Seid Ahmed; Bishaw, Zewdie; Termote, Celine; Fadda, Carlo (International Center for Agricultural Research in the Dry Areas, 2024)
This catalogue is an output of collaborative work of the Genetic Resources Research Institute (GeRRI) of the Kenya Agricultural and Livestock Research Organization (KALRO), the International Center for Agricultural. Research in the Dry Areas (ICARDA), and the Alliance of. Bioversity International and CIAT. The development of the catalogue is funded under the CGIAR Nature Positive Solutions Initiative. The aim of the collaboration is to develop a farmer preferred crop cultivars and varieties catalogue to facilitate registration, quality-declared seed production, certification, and commercialization.